2021
DOI: 10.1007/s43545-021-00069-x
|View full text |Cite
|
Sign up to set email alerts
|

Indulging interactivity: a learning management system as a facilitative boundary object

Abstract: With the recent global pandemic, education institutions including higher education have shifted to offering online instruction for a prolonged period of time. Faculty and instructors have had to transform the content of face-to-face instruction into a format fit for distance education. In the virtual space, understanding or facilitating interactivity is a key component of online teaching for sustaining engagement and social interactions; promoting active learning between participants; and providing resources, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…A survey conducted at Missouri S&T revealed that the main complaint expressed by students, after switching to the online settings, was the lack of interactions either between instructors and students or between students themselves. These findings align with other reported studies [1] on the impact of the recent pandemic on students' learning experiences. During the rapid transition from in-person courses to the online format, many instructors had to eliminate previously designed in-class activities that were proven to be effective in engaging students in class [2][3][4]; others had to adapt activities based on the limitations imposed by the available learning management systems (LMS).…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…A survey conducted at Missouri S&T revealed that the main complaint expressed by students, after switching to the online settings, was the lack of interactions either between instructors and students or between students themselves. These findings align with other reported studies [1] on the impact of the recent pandemic on students' learning experiences. During the rapid transition from in-person courses to the online format, many instructors had to eliminate previously designed in-class activities that were proven to be effective in engaging students in class [2][3][4]; others had to adapt activities based on the limitations imposed by the available learning management systems (LMS).…”
Section: Introductionsupporting
confidence: 93%
“…Interactions occur when these objects and events mutually influence one another". Chang [1] mentioned that an instructor's approach to instructional interactivity has important implications for online teaching. Furthermore, Bickle et.al.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies into IT systems and platforms which support online assessment refer to the importance of features such as assessment Drop Boxes which assist in submitting and tracking assignments, systems which allow students to run their work through Turn-it-in to pick up and rectify unintentional instances of plagiarism prior to final submission and a range of feedback features such as Chat, and synchronous and asynchronous audio and video feedback (Chang & Kuo, 2022;Majid, 2020).…”
Section: Systems and Platforms Which Support Online Assessmentmentioning
confidence: 99%
“…For example, as indicated by Yonghe and Lei (2022), the traditional principle of sustainability of knowledge acquisition should be implemented in any model of distance learning considering the impact of the WEB 2.0 environment on the process of sustainable knowledge acquisition. Another approach is detected in studies by Chang and Kuo (2021), Hamilton et al (2020), and others where the researchers describe the didactic principles primarily on the basis of innovative ICTs, evaluating the features according to their didactic potential. For example, Jensen and Konradsen (2018) explore the immersive learning principle on the example of using head-mounted displays for improving cognitive skills acquisition process.…”
Section: Introductionmentioning
confidence: 99%